Monitoring the effect of water pollution in twelve selected water dams in Osun State of SouthWestern Nigeria (2007)
"The level of water pollution by heavy metals (Cu, Zn,Co, Ni, As, Mn, Cd, Cr, Pb) in twelve selected water Dams in Osun state were determined in order to know their distribution and possible source into the dams. Their bottom sediment and water were collected for analysis. The result in sediment showed that the concentration of manganese is high in all the dams with values ranging from 21, 27-775.99mg/kg and it spreads across all the locations. Cobalt was detected only at one location with concentration of 3.01md/kg. The result in water analysis showed that the concentration of zinc is more than that of manganese, almost in all the dams. The values detected were between 0.0618lng/kg and 0.5068mg/kg while that of manganese was between 0.011 2mg/kg and 0.1887 mg/kg. Cobalt and cadmium were not detected in all the dams. The variation in the concentration of these metals in sediment and water may be due to chemical factors such as solubility, ion exchange ratio and electrochemical deposition. The concentrations of all metals detected were below the standard limit for the heavy metals in surface water according to Regulatory authority Specification. Meanwhile, bioaccumulation of these metals in tissue of the body may be toxic to human health. "